2010
DOI: 10.1080/07481181003697746
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Grief, Anxiety, and Depressive Symptoms in the Use of Bereavement Services

Abstract: This study examined the role of psychological distress in the use of bereavement services at six months post-loss by 250 bereaved spouses in the Changing Lives of Older Couples study. Approximately 52% (129) used services, commonly provided by physicians and clergy. Hierarchical logistic regression analyses indicated that Black race, higher educational level, elevated depressive symptoms, anxiety, and grief were related to greater service use. Other predisposing, enabling, and need variables were not related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 39 publications
2
19
1
4
Order By: Relevance
“…For example, anxiety symptoms were associated with low emotional social support in persons who had experienced a stillbirth [which has been noted as a form of bereavement; 46; 47] and in bereaving spouses [48]. In addition, in observations of widows discussing their emotional reactions to the loss of their spouses, those perceived as less well-adjusted evoked greater frustration and less compassion from onlookers, compared to those who were perceived as better adjusted [49].…”
mentioning
confidence: 99%
“…For example, anxiety symptoms were associated with low emotional social support in persons who had experienced a stillbirth [which has been noted as a form of bereavement; 46; 47] and in bereaving spouses [48]. In addition, in observations of widows discussing their emotional reactions to the loss of their spouses, those perceived as less well-adjusted evoked greater frustration and less compassion from onlookers, compared to those who were perceived as better adjusted [49].…”
mentioning
confidence: 99%
“…There are studies on symptomology, such as in Bergman et al's (2010) examination of psychological distress; those designed to address a type of loss, as shown by Wilkinson et al (2007) who explore child bereavement support services; those in precise settings (Fauri et al, 2000;Roberts & McGilloway, 2008); and others specific to detailed needs in bereavement (Harrison & Harrington 2001, Walsh-Burke 2000. One exception is from Levy and Derby (1992) who compared widowed spouses who join support groups to those who do not.…”
Section: Review Of the Literaturementioning
confidence: 93%
“…The current study's inability to recruit males is representative of several issues. First, previous research has demonstrated that females are more likely to seek bereavement research and services (Bergman, Haley, & Small, 2010). Furthermore, a disproportionately higher number of creative arts therapists are female.…”
Section: Considerations and Recommendationsmentioning
confidence: 99%